Dosimetric impact of interfraction prostate and seminal vesicle volume changes and rotation: A post-hoc analysis of a phase III randomized trial of MRI-guided versus CT-guided stereotactic body radiotherapy. (February 2022) - Ma, Ting Martin; Neylon, Jack; Casado, Maria; Sharma, Sahil; Sheng, Ke; Low, Daniel; Yang, Yingli; Steinberg, Michael L.; Lamb, James; Cao, Minsong; Kishan, Amar U.
Highlights: Prostate volume consistently increased during the course of prostate SBRT. Interfraction prostatic rotation was minimal. Rotation of the proximal seminal vesicle (SV) was considerable. Prostate dosimetry was favorable with 2 mm PTV margin with MRI-guided SBRT. Online adaptive therapy may be indicated to account for proximal SV rotations. Abstract: Background and purpose: Interfraction volumetric changes/rotations in the prostate and proximal seminal vesicles (SVs) might compromise target coverage when tight margins are used for prostate stereotactic body radiotherapy (SBRT). We investigated on-board MRI images from MRI-guided SBRT to better understand this. Materials and methods: Twenty consecutive patients treated with MRI-guided prostate SBRT (40 Gy/5 fractions) enrolled on the MRI arm of a phase III randomized trial were included. A 2 mm isotropic margin was used for prostate and proximal SVPTV. Target volume, prostate dimensions, angles of the proximal SV on axial (angle α) and sagittal view (angle θ) were measured on a 0.35 T simulation MRI and five on-board pre-treatment MRIs. Dice coefficient of the targets and target dosimetry were calculated. Results: All patients experienced an isotropic increase in prostate volume during SBRT ( p  = 0.0016): 0.1%, 9.0%, 12.1%, 15.1%, and 14.2% (median) at fractions 1–5, respectively, regardless of baseline volume, which was significantly reduced with neoadjuvant ADT ( p  = 0.0042). There was minimal interfraction rotation of prostate, however, considerable variations in proximal SV angle α (median 21.5°) and angle θ (median 17.6°) were seen. Median V100% was 97.5% and 87.1% for prostate and proximal SV CTV, respectively. V95%≥95% was achieved in 94% of fractions for the prostate and in 59% for proximal SV. Conclusion: Prostate volume consistently increased during SBRT. Interfraction prostatic rotation was minimal while rotation of the proximal SV was considerable. Prostate dosimetry was favorable, but online adaptive therapy may be indicated occasionally to account for prostatic swelling and in particular proximal SV rotations.